Geographical analysis of water resources and impacts on rural settlements in the channel river of the Betwata valley - Yadgar Mustafa Ibrahim; Shaswar Mohameed Mahmod; Pshtiwan Shfeeq Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The Betwata river channel is a tributary of the lower Zab River in Ranya district. It flows into the lower Zab river 4 km southeast of Sarkhrma village and is located between the latitudes ( ˭0 : ˉ25 : 36˚ ) to ( ˭0 : ˉ10 : 36˚ )the north and the longitudes ( ˭56 : ˉ48 : 44˚ ) to ( ˭44 : ˉ27 : 44˚ ) the east. The source of water for river channel income is located in Ranya district, from each of the streams (Harmk, Sherawa, Betwata, Sarwchawa, Kfradol, and Kani Maran) and receives water from a small part of the beginning of Shaqlawa district. The main objective of this study is to identify the environmental characteristics of the study area and draw a specific map for each of them in order to analyze the impact of water resources and settlement on the human settlements in the study area. such as: (geology, altitude, climate, water resources, soil and vegetation cover). In the second part, we analyze the water resources and the impact on human settlements according to (distribution of rural settlements in order of size and stability of human settlements according to springs, rivers, and streams; type of distribution on the basis of nearest neighbour). The results show that the natural characteristics of the study area play a main role in the richness of water resources and affect the size and distribution of rural settlements.